Mechanical and thermal behavior of polyvinyl alcohol reinforced with aligned carbon nanotubes - Medina Escobar,Sergio Alonso (2015)
ABSTRACTIn recent years, due to their high specific mechanical properties, the polymer matrix composites have been widely used. In particular, carbon nanotubes (CNTs) have been used as reinforcement due to its exceptional mechanical and electrical properties. In this work the mechanical behavior of polyvinyl alcohol (PVA) reinforced with different percentages of mechanically oriented CNTs was studied. The composite material was made starting with a solution of PVA+ distilled water, and then the CNTs were added to the solution and dispersed by magnetic stirring and ultrasonic agitation. During this step, a surfactant was added to help with the CNTs dispersion. This mixture was poured into a container and dried using a heat source to accelerate its polymerization and curing. The layers obtained were subjected to mechanical stretching at controlled temperature to align the CNTs in the loading direction. The mechanical properties were measured by tensile testing and nanoindentation. The results show a large increase in modulus and hardness compared with non-reinforced polymeric material, it was also found a significant increase in the tensile strength. The composite with the best properties was subjected to thermal stabilization by ethanol, obtaining an increase in the degradation temperature of about 100°C approximately, although in this case the mechanical stiffness and hardness were decreased compared to unstabilized material, the usefulness of this material is enhanced.